Life cycle assessment of atmospheric environmental impact on the large-scale promotion of electric vehicles in China - Haoran Shang; Yutong Sun; Desheng Huang; Fanxin Meng (Resources, Environment and Sustainability, 2024)
Decarbonizing the transportation sector emerges as a pivotal step in addressing climate change. In recent years, rapid growth in China’s new energy automotive industry has significantly contributed to transportation decarbonization. However, environmental challenges in producing and recycling electric vehicles (EVs) may limit emission reduction benefits. In this study, we establish a comprehensive life cycle assessment model for vehicles to analyze the gap in air pollutant and greenhouse gas emissions between electric vehicles and internal combustion engine vehicles (ICEVs). Based on this model, the environmental benefits of further promoting electric vehicles in China are evaluated. Results reveal that, compared to ICEVs, EVs reduce life cycle emissions of CO2 by 12%, NOx by 69%, and VOCs by 9%. Primary constraints on EVs in emission reduction are traced to raw material and component production, notably lithium batteries. By 2025, under the low carbon EVs policy scenario, widespread EV production and sales could cut lifecycle emissions by 3.55 million tons of CO2, 3,6289 tons of NOx, and 4315 tons of VOCs. During the driving stage, these indicators contribute 495%, 124%, and 253%, respectively, to total emission reduction throughout the lifecycle. This study conducts a comprehensive lifecycle analysis of greenhouse gases and various air pollutants for Chinese EVs. It integrates the latest market trends, application progress, and policy guidelines into scenario design, identifying key sources and indicators of atmospheric pollution in the EV production chain. The findings offer valuable policy insights into China’s role in the global emission reduction process.